Promoting a healthy and smart living community in rational use of medicine at RW 05 Kebun Jeruk, West Jakarta - Ratih Dyah Pertiwi; Anisa Uswatun Khasanah; Yolanda Yolanda; Novi Andriani; Teti Maharani; Tasya Nurmila Devi; Dwi Evi Indriani; Wahyu Darmawan; Dewi Puji Astuti (Universitas Muhammadiyah Magelang, 2022)
Omicron is a large family of corona viruses that can cause illness ranging from mild to severe symptoms. This severe symptom of Covid-19 will be worrying if it afflicts erderly and toddlers. Lack of knowledge about proper medication use, health precautions, and the importance of handwashing are some of the issues that exist in the community of RW 05 Kebon Jeruk. Based on the survey, it is necessary to carry out community service which aims to determine public knowledge in responding to the Covid-19 pandemic. In addition, it also monitors public knowledge about the rational use of drugs and children's knowledge about the importance of keep healthy. The methods used in this program are door-to-door counseling and education, question and answer and discussion, coloring competition and socialization of little pharmacists, posyandu, morning exercise, delivery of family medicinal plants, and distribution of new normal kit packages. According to questionnaires, education, and other activities, the public's understanding of rational medicine, children's understanding of the importance of keep healthy, and the public's understanding of how to respond to the pandemic period have all increased.